Abnormal levels of apolipoprotein A‐I in chronic thromboembolic pulmonary hypertension. (1st April 2021) - Khirfan, Ghaleb; Li, Manshi; Wang, Xiaofeng; DiDonato, Joseph A.; Dweik, Raed A.; Heresi, Gustavo A.
Abstract : Recent studies have shown low high‐density lipoprotein cholesterol (HDL‐C) and dysregulated lipid metabolism in chronic thromboembolic pulmonary hypertension (CTEPH). Apolipoprotein A‐I (ApoA‐I) is the major protein component of HDL‐C and mediates most of its functions. We hypothesize that ApoA‐1 and its oxidative state might be more sensitive biomarkers in CTEPH. Plasma levels of HDL‐C, ApoA‐I, paraoxonase‐1 enzyme activity (PON1), and the oxidized dysfunctional ApoA‐I (oxTrp72‐ApoA‐I) were measured in patients with CTEPH and compared to those in healthy controls. Association with markers of disease severity in CTEPH was assessed. We included a total of 61 patients with CTEPH (age: 61.2 ± 15 years; male 52.5%) and 28 control subjects (age: 60.1 ± 8 years; male 59.3%). When adjusting for age, sex, body mass index, and statin use, ApoA‐I was lower in CTEPH compared to controls (CTEPH:125.2 ± 27 mg/dl; control:158.3 ± 29.4 mg/dl; p < 0.001), but HDL‐C levels were not statistically different. There were no significant differences in PON and oxTrp72‐ApoA‐I/ApoA‐I ratio. In exploratory analyses, ApoA‐I was associated with mean right atrial pressure (rs = −0.32, p = 0.013) and N‐terminal pro B‐type natriuretic peptide (rs = −0.31, p = 0.038). There were no significant associations between HDL‐C, PON1, or oxTrp72‐ApoA‐I/ApoA‐I ratio and markers of disease severity. We conclude that ApoA‐I is a more sensitive biomarker than HDL‐C in CTEPH, and may be associated with right heart dysfunction.